(untitled) (Indian Journal of Arid Horticulture, 2025)
The Chakaiya variety of aonla was pre harvest sprayed with CaCI, GA, and their combinations. Full mature fruits were harvested and stored at ambient temperature (7.48-21.34°C). The findings suggest that fruits can be stored at ambient temperature for 5 days without any treatment whereas shelf life can be prolonged upto 20 days with 15.62 per cent decay loss by spraying 2% CaCl, + 100 ppm GA, 25 days before harvesting of the fruits.The lowest PLW, higher T.S.S., maximum retention of ascorbic acid, higher reducing sugar, non-reducing sugar, total sugars and phenols were also estimated in 2% CaCl,+100 ppm GA, treated fruits.